KEANEKARAGAMAN JENIS DAN POLA SEBARAN KANTONG SEMAR (NEPENTHES SPP) DI BUKIT BENUA KABUPATEN KUBU RAYA - Sintaro, Emo; Kartikawati, Siti Masitoh; Darwati, Herlina (JURNAL HUTAN LESTARI, 2016)
Nepenthes plants iniluding groud lianas (vines), married two and separate male and female ftowers on the different individual. Lite in the gronnd or attached to the trunk or branches of the other trees. Nepenthes are living in the open or shelter or poor nutrient habitats and having a furly high humidity. The purpose was determining diversity of types pitcher of plants, Nepenthes habitat of conditions are existing on Bukit Benua and distribution in pattern. The analysis results of date obtained six types pitches of plants like that Nepenthes ampullaria, N mirabilis, N gracilis, xkuchingensis, N xhookeriana and xneglecta with 592 individuals. Nepenthes condition habitat has found in the open location 413 individuals, shade has found 118 individuals and shaurd location has found 61 individuals the value of the hinghes species diversity (. N ampullaria of 0,15, whereas N xneglecta is very little of 0,07. Index value everneass (e) is very leind haighest N ampullaria 0,20, N xneglecta is very small 0,09. Pattren nepenthes of distribution in Bukit Benua in all groups because of the greater is than 1.Key words : Distribution of nepenthes.